De capela a coreto : direito à memória negra e (re)apropriação na Praça Coronel Chico de Sá - Pirenópolis (GO) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The present study, inserted in the line of research Culture, Preservation, and Identities, considers as guiding events that can be problematized: the Capela de Nossa Senhora do Rosário dos Pretos erection, from 1743 when Pirenópolis still held the position of Arraial and was called Minas de Nossa Senhora do Rosário de Meia Ponte; this temple demolition in the 40s; and the multiple meanings of the place, from its first uses, when black brotherhoods there manifested religiosity and ways of resistance in the colonial context, to its current uses, caused by the modification of space and construction of Praça Coronel Chico de Sá (Praça do Coreto), in the 80s. From these events, we seek to check if Praça do Coreto can be viewed as a cultural heritage that helps in the maintenance and perception of the black contribution in the identity construction of Pirenópolis, as well as a potential problematizing territory of heritage narratives, which, influenced by the coloniality of power, historically excluded black heritage from institutional selections. To achieve the proposed objectives, in addition to bibliographic and documentary analysis, we adopted research techniques, considering the internal actors (residents of Pirenópolis) and external actors (tourists), the application of surveys, and the realization of unstructured interviews. We assume that the Praça do Coreto, according to its multiple territorialities, which can be motivated by the past or externalized due to the present context, can be considered a cultural asset that propels the right to black memory from the awareness, participation, and preservation arising from the subjects which they use, value and (re)appropriate the place, regardless of the motivation for this (re)appropriation. As a research product, we idealized a virtual museum of a continuous, repository, and collaborative nature called Coremória, which aims to bring together media and memories related to the cultural assets studied.
From capela to coreto: right to black memory and (re)appropriation in Praça Coronel Chico de Sá - Pirenópolis (GO)
Keywords: Capela de Nossa Senhora do Rosário dos Pretos; Memória; Patrimônio negro; Pirenópolis; Praça do Coreto; Memory; Black heritage; CIENCIAS HUMANAS::HISTORIA